2011
DOI: 10.1111/j.1755-3768.2011.02226.x
|View full text |Cite
|
Sign up to set email alerts
|

The post‐illumination pupil response of melanopsin‐expressing intrinsically photosensitive retinal ganglion cells in diabetes

Abstract: ABSTRACT.Purpose: This study investigates the clinical utility of the melanopsin-expressing intrinsically photosensitive retinal ganglion cell (ipRGC) controlled postillumination pupil response (PIPR) as a novel technique for documenting inner retinal function in patients with Type II diabetes without diabetic retinopathy. Methods: The PIPR was measured in seven patients with Type II diabetes, normal retinal nerve fibre thickness and no diabetic retinopathy compared to healthy age-similar controls. A 488-and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 31 publications
4
100
2
2
Order By: Relevance
“…It is also believed that the ipRGCs influence an intrinsic retinal circadian clock to regulate retinal melatonin levels by both exogenous light stimulation and endogenous circadian stimulation) [41]. The effects that the ipRGC have on degenerative processes are studied in diseases such as glaucoma and diabetes [42].…”
Section: Non-image Forming Systemsmentioning
confidence: 99%
“…It is also believed that the ipRGCs influence an intrinsic retinal circadian clock to regulate retinal melatonin levels by both exogenous light stimulation and endogenous circadian stimulation) [41]. The effects that the ipRGC have on degenerative processes are studied in diseases such as glaucoma and diabetes [42].…”
Section: Non-image Forming Systemsmentioning
confidence: 99%
“…55,104 In patients with type 2 diabetes, ipRGC dysfunction has been proposed to be investigated for diagnostic purpose by using the postillumination pupil response (PIPR), a sustained constriction of the pupil after light offset. 105 The classic hallmark of glaucomatous optic neuropathies is the progressive loss of RGCs and their axons, with concomitant insidious defects in the visual field. As for RGCs, ipRGC abnormalities have been reported in rodent models of experimental glaucoma [106][107][108][109] and in glaucomatous patients.…”
mentioning
confidence: 99%
“…While their involvement in AMD is currently not fully understood, pilot data indicate that they are dysfunctional in late stages of the condition . Whether they are affected in early AMD as has been shown for glaucoma (Adhikari, Zele, Thomas & Feigl 2016b) and in diabetes without retinopathy (Feigl et al 2012b) is yet to be determined. The choroid lies posterior to the retina and is separated from the retinal pigment epithelium (RPE) by Bruch's membrane (BM).…”
Section: Statement Of Original Authorshipmentioning
confidence: 99%
“…IpRGCs also signal to the olivary pretectal nucleus (OPN) for mediation of the pupil light reflex (PLR) (Gamlin et al 2007;Kawasaki & Kardon 2007) and in particular the post-illumination pupil response (PIPR) (Adhikari et al 2016a;Gamlin et al 2007;Kawasaki & Kardon 2007;Markwell et al 2010), which is an emerging method for the direct assessment of ipRGC function in healthy and diseased eyes and in persons with chronobiological disorders Feigl et al 2012b;Gamlin et al 2007;Gracitelli et al 2016;Gracitelli et al 2014;Gracitelli et al 2015;Kawasaki & Kardon 2007;Markwell et al 2010;Maynard et al 2015). Two recent studies observed that sleep duration was altered in advanced AMD patients; sleep duration decreased in wet AMD and increased in dry AMD (Khurana et al 2016;Pérez-Canales et al 2016) but the effect of aberrant ipRGC signalling in AMD Maynard et al 2015) as a contributing factor was not evaluated.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation